Outcome Analysis of Day-Care vs. Inpatient Breast Lump Excision Surgeries - Wajahat Hussain, Junaid Hassan, Amina Israr, Inayat Husain Anjum, Muhammad Tariq Bashir, Abid Raza (International Journal of Pharmacy Research & Technology (IJPRT), 2025)
This prospective cohort study compares surgical outcomes, patient satisfaction, cost-effectiveness,and complication rates between day-care and inpatient breast lump excision in 150 adult women.Patients were assigned to either day-care (n=75) or overnight-stay inpatient (n=75) pathways.Primary outcomes included postoperative complications (seroma, hematoma, infection)